(untitled) (ACTA MEDICA PERUANA, 2020)
Objectives: To analyze and discuss barriers for diagnosis and therapy of cervical cancer (CC) in a public hospital in Lima, Peru. Materials and methods: A qualitative study was performed between December 2019 and March 2020. Observation and detailed interviews were the data collection tools used. In total, 15 detailed interviews with patients and healthcare personnel were carried out. Results: For healthcare personnel interviewed, barriers (for good care) are basically lack of personnel and poor hospital infrastructure. This leads to weakening educational campaigns with respect to the importance of adequate screening for CC prevention. For patients, time limitations, lack of knowledge and fear of being exposed to a male healthcare worker are the main barriers for healthcare proper decision making with respect to CC prevention and management. Conclusions: The weak Peruvian hospital infrastructure influences educational and promotional activities dedicated to CC. There is also an impact of the time for obtaining results of screening tests and access to gynecological consultation. These delays lead to absence and discontinuation in women self care. All this, additionally to lack of knowledge about CC severity by patients, and also because of prioritization of their working and household tasks, may lead us to reflect on an insufficient performance of our healthcare system with respect to management of this disease.